Hunting scene on pillar capital - Ghosh, Ayan (Jio Institute, 2023)
Animal figures feature extensively on the BMC building. They are often camouflaged within the dense floral motifs on pillar capitals. The animals are found in Mumbai and provide an important local context to the buildings, representing the ecological diversity of the region. They include squirrels, owls, herons, monkeys, snakes, peacocks, rats and other animals.